Allogeneic hematopoietic stem cell transplant overcomes the adverse survival effect of very high risk and unfavorable karyotype in myelofibrosis. Issue 5 (24th February 2018) - Tefferi, Ayalew; Partain, Daniel K.; Palmer, Jeanne M.; Slack, James L.; Roy, Vivek; Hogan, William J.; Litzow, Mark L.; Ketterling, Rhett P.; Patnaik, Mrinal M.
Abstract: The prognostic importance of genetic information in primary myelofibrosis (PMF) was recently highlighted in a study of over 1000 cytogenetically‐annotated patients; 5‐year survival rates were 8% for very high risk (VHR), 27% "unfavorable" and 45% "favorable" karyotype. The current study addresses the practice‐relevant question of whether or not allogeneic hematopoietic stem cell transplant (HCT) can overcome the detrimental survival effect of VHR or unfavorable karyotype. The study included 67 patients with PMF or secondary MF who received HCT at the Mayo Clinic and in whom pretransplant cytogenetic information was available. Dynamic international prognostic scoring system (DIPSS) risk distribution was 13% high, 66% intermediate‐2 and 21% intermediate‐1. Cytogenetic risk distribution was 11% VHR, 34% unfavorable and 55% favorable. At median post‐HCT follow‐up of 60 months for living patients (range 34‐170), 28 (42%) deaths were recorded. Five‐year survival was 62% and was not affected by VHR or unfavorable karyotype ( P  = .68). The salutary effect of HCT in patients with VHR or unfavorable karyotype was also apparent during analysis of a combined dataset that included a nontransplant cohort of 383 patients with PMF; multivariable analysis of the combined dataset ( n  = 450) resulted in HRs (95% CI) of 2.4 (1.6‐3.6) for absence of transplant, 3.3 (2.2‐4.8) for VHR karyotype, 1.6 (1.2‐2.1) for unfavorable karyotype, 2.9 (2.0‐4.2) for DIPSS high and 1.7 (1.4‐2.2) for DIPSS intermediate‐2. These observations were further confirmed by analysis of more stringently matched case‐control subset cohorts and provide the evidence for the therapeutic preference of HCT in cytogenetically high risk patients with MF.